Неявный численный метод для моделирования нестационарного несжимаемого течения жидкости - Русанов, Андрей Викторович; Быков, Юрий Адольфович (НТУ "ХПИ", 2017)
Представлен неявный численный метод для моделирования трехмерных нестационарных несжимаемых течений жидкости в проточных частях гидромашин. Метод основан на применении концепции искусственной сжимаемости с дополнительными итерациями на каждом временном шаге. Разностная схема имеет второй порядок аппроксимации по пространственным координатам и времени. Представлены результаты моделирования одномерного нестационарного течения, для которого имеется аналитическое решение. Проведенный анализ данных численного моделирования демонстрирует возможность использования предложенного метода для расчета нестационарных течений в проточных частях гидромашин.

An implicit numerical method for simulating three-dimensional unsteady incompressible fluid flows in hydraulic machines flow parts of is presented. The method is based on the exploitation of the concept of artificial compressibility with additional iterations at each time step. The difference scheme has the second order approximation for spatial coordinates and time. The presented numerical method is integrated into the software package IPMFlow, which developed for numerical simulation of three-dimensional viscous flows in flow parts of turbomachines of various types. The simulation results of a one-dimensional unsteady fluid flow in a channel for which there is an analytical solution are presented. The obtained results of numerical simulation are in good agreement with the data of the analytical solution. The analysis of numerical simulation data demonstrates the possibility of using the proposed method for calculating unsteady flows in hydraulic machines flow parts.
An implicit numerical method for unsteady incompressible fluid flow simulation
Keywords: численное моделирование; математическая модель; искусственная сжимаемость; расчетные сетки; numerical simulation; mathematic modeling; artificial viscosity; incompressible fluid; unsteady flows; computing meshes